2014
DOI: 10.1007/s00210-013-0952-2
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiology and pharmacology of tandem domain potassium channel TREK-1 related BDNF synthesis in rat astrocytes

Abstract: In the present study, the functional properties and pharmacology of two-pore domain potassium channel (K2P) TREK-1 in primary cultured rat brain astrocytes were investigated. Western blot, patch clamping techniques, and ELISA were used to detect the distribution and function of TREK-1 as well as the expression of brain-derived neurotrophic factor (BDNF) on the primary cultured astrocytes. It was shown that TREK-1 protein expressed in astrocytes was 2.4-fold higher than it was expressed in microglia. Single cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 41 publications
0
6
0
1
Order By: Relevance
“…Another key role of astrocytes is the maintenance and survival of neurons through BDNF, and increased BDNF levels have been linked to treatment of astrocytes with certain TREK-1 antagonists (Lu et al, 2014). This could occur from an upregulation of PKA-CREB-BDNF signaling via TREK-1 to increase 5-HT transmission (Shirayama et al, 2002;Ye et al, 2015), or to increase cell viability and hippocampal neurogenesis to elicit an antidepressant-like response (Heurteaux et al, 2006;Zhou et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Another key role of astrocytes is the maintenance and survival of neurons through BDNF, and increased BDNF levels have been linked to treatment of astrocytes with certain TREK-1 antagonists (Lu et al, 2014). This could occur from an upregulation of PKA-CREB-BDNF signaling via TREK-1 to increase 5-HT transmission (Shirayama et al, 2002;Ye et al, 2015), or to increase cell viability and hippocampal neurogenesis to elicit an antidepressant-like response (Heurteaux et al, 2006;Zhou et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…One study reports that activation of the BDNF pathway controls the morphology of cytoskeletal changes in astrocytes [ 34 ]. Moreover, previous research demonstrates that the synthesis of BDNF is enhanced following the inhibition of TREK-1 [ 35 ]. In the present study, we also found that the knockdown of TREK-1 increased the level of BDNF following isoflurane-induced astrocytic injury, and we thus inferred that BDNF participated in the protective effects associated with decreased TREK-1 levels following isoflurane-induced astrocytic cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…This is of significance because astrocytes not only sense nutrients and hormones, but also are known to regulate action potential generation and pattern in neuronal circuits. 13,14 Historically, in vivo studies have predominantly used extracellular, single unit or intracellular sharp electrode recording configurations because movement of the brain in response to blood flow was less likely to disrupt the recording. In comparison, even the slightest movement can disrupt a patch clamp recording pipette seal.…”
Section: F I G U R E 1 Major Electrophysiological Recording Configurations Used To Investigate the Effects Of Glucose And Insulin On Neurmentioning
confidence: 99%